Entry diversion: Deterrence by diverting submarket entry - Uzunca, Bilgehan; Cassiman, Bruno (Strategic Management Journal, 2023)
Abstract Research Summary Going back to Bain (1956), strategy scholars have long recognized the importance of deterring entry for sustaining incumbents' profits in an industry. We introduce a new mechanism, entry diversion , to better understand the empirical phenomenon of persistent firm entry in spite of investments in entry deterrence by incumbents in some industries. Entry diversion happens when preemptive strategic investments by incumbents decrease the expected future profits from a target submarket such that entrants choose to enter another submarket within the same industry. Empirical evidence from the global semiconductor manufacturing industry suggests that incumbents expand their capacities beyond demand growth, and that these investments effectively divert entry into other submarkets. Greenfield entrants are more responsive to entry diversion than incumbents. Managerial Summary Managers have long understood that deterring entry of new players into their industry could sustain their firms' profits. In this article, we introduce a new mechanism, entry diversion, where the incumbent diverts potential entrants from its submarket toward other submarkets in the same industry. Entry diversion happens when preemptive strategic investments by incumbents decrease the expected future profits of the entrant in a submarket of the industry such that the entrant chooses not to enter the incumbent's submarket. Contrary to entry deterrence, new players will still enter the industry but settle in different submarkets. Empirical evidence from the global semiconductor manufacturing industry suggests that incumbents expand their capacities beyond demand growth, and that these investments effectively divert entry into other submarkets.